Factors affecting knowledge sharing among ESL undergraduates in completing collaborative writing tasks using Wiki and Skype - Hiew, Yolanda; Tan, Bee Hoon (Malaysian English Language Teaching Association, 2014)
Computer-mediated communication (CMC) has become increasingly necessary in tertiary education as it supports collaborative learning among students. Hence, interaction using social networks such as email, Facebook, Wiki and Skype, provides a way for students to collaborate and share knowledge about their studies outside the classroom. However, using CMC tools where English is used as the medium of communication in completing collaborative writing tasks can be a challenge to ESL students. Studies have explored the factors that affect students' participation and knowledge sharing in online collaborative learning such as social presence, trust, conflict, mutual influence, cohesion, and team leadership. Thus, this study aimed to find out which factors affect students' knowledge sharing in online collaboration, and to identify which CMC tools benefit or limit collaborative learning. Twenty five ESL undergraduate English Language major students participated in the study. The data was collected through a questionnaire distributed to students after they completed two project- based writing tasks asynchronously on Wiki and synchronously on Skype. The results of the study revealed that social presence and team leadership are significantly affecting knowledge sharing through online collaborative learning, and students' participation in online interaction is highly related to social presence and team leadership. Moreover, students indicated that Skype is more beneficial for collaborative learning, though they implied that Wiki can improve writing skills.